QIShLOQ XOʻJALIGI TARKIBINI OPTIMALLAShTIRISh OMILLARI (Qoraqalpogʻiston tabiiy sharoiti misolida) - Yeshimbetov, U.X. (SCIENCE and SOCIETY, 2025)
The article examines the factors of optimal location of agriculture using the example of the natural conditions of Karakalpakstan. The article also discusses some theoretical aspects of the location of agriculture.
Keywords: agriculture; location; natural conditions; animal husbandry; division of labor; branch; specialization; territorial organization